The Effectiveness and Safety of Acupuncture for Patients With Alzheimer Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 22 (June 2015) - Zhou, Jing; Peng, Weina; Xu, Min; Li, Wang; Liu, Zhishun
Abstract : Abstract: The use of acupuncture for treating Alzheimer disease (AD) has been increasing in frequency over recent years. As more studies are conducted on the use of acupuncture for treating AD, it is necessary to re-assess the effectiveness and safety of this practice. The objective of this study was to assess the effectiveness and safety of acupuncture for treating AD. Central Register of Controlled Trials (CENTRAL), PubMed, MEDLINE, Embase, PsycINFO, Chinese Biomedicine Literature (CBM), Chinese Medical Current Content (CMCC) and China National Knowledge Infrastructure (CNKI) were searched from their inception to June 2014. Randomized controlled trials (RCTs) with AD treated by acupuncture or by acupuncture combined with 1 kind of drugs were included. Two authors extracted data independently. The continuous data were expressed as mean differences (MD) with 95% confidence intervals (CIs). Weighted MD (WMD) was used instead of standardized MD (SMD) when the same scales were used. Adverse reactions related to acupuncture were also investigated. Ten randomized controlled trials with a total of 585 participants were included in the meta-analysis. The combined results of 6 trials showed that acupuncture was better than drugs at improving scores on the Mini Mental State Examination (MMSE) scale (MD 1.05, 95% CI 0.16–1.93). Evidence from the pooled results of 3 trials showed that acupuncture plus donepezil was more effective than donepezil alone at improving the MMSE scale score (MD 2.37, 95% CI 1.53–3.21). Out of 141 clinical trials, 2 trials reported the incidence of adverse reactions related to acupuncture. Seven out of 3416 patients had adverse reactions related to acupuncture during or after treatment; the reactions were described as tolerable and not severe. Acupuncture may be more effective than drugs and may enhance the effect of drugs for treating AD in terms of improving cognitive function. Acupuncture may also be more effective than drugs at improving AD patients' ability to carry out their daily lives. Moreover, acupuncture is safe for treating people with AD. Protocol registration: PROSPERO CRD42014009619. Protocol published in BMJ-open.